2001
DOI: 10.1093/emboj/20.24.6937
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane composition of a lipopolysaccharide-deficient Neisseria meningitidis mutant

Abstract: In the pathogen Neisseria meningitidis, a completely lipopolysaccharide (LPS)-de®cient but viable mutant can be obtained by insertional inactivation of the lpxA gene, encoding UDP-GlcNAc acyltransferase required for the ®rst step of lipid A biosynthesis. To study how outer membrane structure and biogenesis are affected by the absence of this normally major component, inner and outer membranes were separated and their composition analysed. The expression and assembly of integral outer membrane proteins appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 58 publications
11
107
1
Order By: Relevance
“…By electron microscopy, RBs in cells treated with LpxC inhibitors displayed normal outer and inner membranes, with no obvious differences in membrane thickness compared with untreated infected cells, as has been reported for N. meningitidis lpxA mutants (29). In these Neisseria mutants, the distribution of phosphatidylethanolamine and phosphatidylglycerol in inner and outer membranes was not affected, but their fatty acyl chains showed a shift toward shorter-chain saturated fatty acids (31). Future work will be aimed at determining if Chlamydia undergoes a similar adaptation upon treatment with LpxC inhibitors.…”
Section: Discussionsupporting
confidence: 69%
“…By electron microscopy, RBs in cells treated with LpxC inhibitors displayed normal outer and inner membranes, with no obvious differences in membrane thickness compared with untreated infected cells, as has been reported for N. meningitidis lpxA mutants (29). In these Neisseria mutants, the distribution of phosphatidylethanolamine and phosphatidylglycerol in inner and outer membranes was not affected, but their fatty acyl chains showed a shift toward shorter-chain saturated fatty acids (31). Future work will be aimed at determining if Chlamydia undergoes a similar adaptation upon treatment with LpxC inhibitors.…”
Section: Discussionsupporting
confidence: 69%
“…5B), indicating that the LPS produced in this strain was not accessible to PagL in the OM. Previously, it was reported that LPS depletion has no effect on assembly of OMPs in N. meningitidis (13), but to verify that the PagL produced in the imp mutant was functional, we determined PagL activity in membrane preparations. Cell envelopes containing or lacking PagL were incubated with purified LPS of the L3 immunotype and the modification of this LPS was assessed by Tricine-SDS͞ PAGE (Fig.…”
Section: Phenotype Of a Neisserial Imp Mutantmentioning
confidence: 99%
“…The capsular polysaccharide from serogroup B meningococci is an α-2,8-linked polysialic acid moiety mimetic of many human glycoproteins including the neural cell adhesion molecules (NCAM). As an alternative approach, outer membrane vesicles (OMV) vaccines depleted of lipooligosaccharide (LOS) to prevent local severe reactogenicity have been developed [4,5] and other protein vaccines containing overexpressed or tailored OMP(s) are under study but OMV vaccines devoid of endotoxin are poorly immunogenic [6].…”
Section: Introductionmentioning
confidence: 99%